RANCANG BANGUN SISTEM INFORMASI PENDAFTARAN PESERTA DIDIK PADA MADRASAH TSANAWIYAH AR-RASYIDIYYAH JAKARTA UTARA - Fahrizal; Ahmad Zulfahmi (POLITEKNIK LP3I JAKARTA, 2024)
The rapid development of information technology has encouraged various educational institutions to utilize digital-based systems to support their operational activities, one of which is the student registration process. The registration process, which is still carried out manually, requires prospective students or applicants to come directly to the registration location, which is considered ineffective and inefficient in terms of time, energy, and data processing. Therefore, a system is needed that can help registrants complete the student registration process online without having to come to the registration location. This study aims to design and develop a web-based student registration system that can make it easier for registrants to complete the registration process and help schools manage registration data in a more organized manner. With this system, the process of accepting new students is expected to be more effective, efficient, and accurate. The system design was carried out using Unified Modeling Language (UML) as a system modeling tool, while the data architecture design used Entity Relationship Diagram (ERD) and Logical Record Structure (LRS). The system implementation used the PHP programming language with the support of HTML and CSS as the interface designer. The results of this study are expected to be a solution in improving the quality of student registration services in schools.